The Application and Challenges of Earned Value Management (EVM) As Cost Monitoring Tool in the Construction Industry - Sunarti, Noorhidayah; Pakir Mastan, Zetty; Seon Cin, Lum (International Journal of Engineering and Technology, 2018)
Earned Value Management (EVM) is one of the fundamental approaches acting as a comprehensive project management and controlling technique for tracking the costs and examining project expenditures relative to the physical progress of work. Majority of the previous literature reviews and findings indicates the positive contributions of EVM in monitoring the project time-cost performance progressively and forecasting its future trends. However, EVM was not widely used as practically, the traditional cost and schedule monitoring tool is still very common in the construction industry. Thus, this research was conducted using quantitative method to the identified quantity surveying, project management and construction firms in Klang Valley area to achieve the objectives of; (1) to identify the implementation level of EVM in construction projects, (2) to recognize the EVM contribution as cost monitoring tool compared to the other mehods, and (3) to ascertain the challenges in using EVM. Based on the result, majority has reaffirmed that EVM is positively contribute to project cost monitoring and provide an overall effective cost management tools in their projects. Despite the major challenges identified in using EVM are due to the lack of EVM knowledge, expertise and experience by the user in the industry, the results also indicating that more construction players have come to realize that integration of cost and time management in EVM is beneficial to the construction industry.Â Â